Hybrid MBSE-DevOps model for implementation in very small enterprises - Simpson, Cailin R., author; Simske, Steven, advisor; Miller, Erika, committee member; Reisfeld, Brad, committee member; Sega, Ronald, committee member (Colorado State University. Libraries, 2024)
This work highlights the challenge of implementing digital engineering (DE) practices, specifically model-based systems engineering (MBSE) and DevOps, in very small entities (VSEs) that deliver software products. VSEs often face unique challenges due to their limited resources and project scale. Various organizations have authored strategies for DE advancement, such as the Department of Defense's Digital Engineering Strategy and INCOSE's System Engineering 2035 that highlight the need for improved DE practices across the engineering fields. This work proposes a hybrid methodology named FlexOps, combining MBSE and DevOps, to address these challenges. The authors highlight the challenges faced by VSEs and emphasize that MBSE and DevOps adoption in VSEs requires careful consideration of factors like cost, skill availability, and customer needs. The motivation for the research stems from the difficulties faced by VSEs in implementing processes designed for larger companies. The authors aim to provide a stepping stone for VSEs to adopt DE practices through the hybrid FlexOps methodology, leveraging existing MBSE and DevOps practices while accommodating smaller project scales. This work emphasizes that VSEs supporting government contracts must also adopt DE practices to meet industry directives. The implementation of FlexOps in two case studies highlights its benefits, such as offering a stepping stone to DE practices, combining Agile, MBSE, and DevOps strategies, and addressing VSE-specific challenges. The challenges faced by VSEs in adopting DE practices may be incrementally improved by adopting a hybrid method: FlexOps. FlexOps was designed to bridge the gap between traditional practices and DE for VSEs delivering software products.